Effect of intra articular tranexamic acid at different doses in unilateral total knee arthroplasty - Peerally, Mohammad Furrhaan (2018)
Introduction: Tranexamic acid is routinely used to reduce blood loss in some dental and cardiac surgeries. Several studies have demonstrated similar effect in total knee arthroplasty surgery, but the route of administration, regimen used and dosage have been quite variable, ranging from single intra-articular dose of 1.5 gram to a triple intravenous dose of 3 grams. This study has been designed to compare the effect of intra-articular irrigation of tranexamic acid in reducing blood loss in unilateral total knee arthroplasty surgery at 3 different doses (1, 2 and 3 grams). Methodology: This was a prospective, randomised, single blinded study involving 57 patients, undergoing unilateral total knee replacement surgery in HUSM. Each patient received a randomised intra-articular dose of either 1 , 2 or 3 grams of tranexamic acid before joint closure and tourniquet release. Randomisation was done by a web-based software. Each patient received the same volume inside their knee joint (tranexamic acid + normal saline made up to 30 mL). Group 1 received 1 gram of tranexamic acid, group 2 received 2 grams of tranexamic acid and group 3 received 3 grams of tranexamic acid. An intra-articular drain size 12 was inserted for each patient and connected to the vacuum drain bottle which was opened 4 hours after surgery for tamponade effect. The pre-operative and 48 hours postoperative haemoglobin and haematocrit level, as well as the volume of drain output at 24 and 48 hours were recorded for each patient. The mean difference between pre-operative and post-operative haemoglobin and haematocrit level and the mean volume of drain output at 24 and 48 hours were calculated and analysed by SPSS version 20.0 and compared using one way ANOVA analysis. Results: The mean difference between pre-operative and post-operative haemoglobin for group 1, 2 and 3 grams were 1.36g/dL,1.40g/dL and 1.23g/dL respectively (p value 0.747).The mean difference between preoperative and postoperative haematocrit for group 1,2 and 3 grams were 4.15%.4.26% and 4.27% respectively (p value 0.950). The mean volume of drain output at 48 hours for group 1,2 and 3 grams were 336.84 mL,313.68 mL and 263.68 mL respectively(p value 0.195). Conclusions: There was no significant difference in the amount of blood loss among the 3 doses of tranexamic acid (1, 2 or 3 grams) when it was used as a single intra-articular administration before wound closure in unilateral total knee arthroplasty. This can turn out to be a cost effective finding in the long run for the inpatient management of those undergoing TKR.